Biomonitoring in wearers of permethrin impregnated battle dress uniforms in Afghanistan and Germany. Issue 2 (16th December 2013) - Kegel, Peter; Letzel, Stephan; Rossbach, Bernd
Abstract : Objectives: To analyse differences in uptake of the insecticide permethrin in wearers of non-impregnated and permethrin impregnated battle dress uniforms (BDU) in Afghanistan and Germany. Methods: In two separate studies, in April 2003–January 2004 (study I, n=549) and in February–April 2005 (study II, n=195), healthy female and male members of the German Federal Armed Forces were equipped with permethrin impregnated BDU (two sub-cohorts in Germany and one in Afghanistan) while members equipped with non-impregnated uniforms served as a control group. Human biomonitoring was conducted before, during and after wearing the uniforms by measuring permethrin metabolites in urine samples via GC–MS. Results: Subjects of the Afghan and German control groups had permethrin levels in the range of the German general population. In contrast, subjects wearing impregnated BDU had about 200-fold higher exposure levels. Within this group, subjects located in Afghanistan and smokers had significantly higher exposure levels. Internal exposure decreased with increasing duration of use of impregnated BDU. Conclusions: There is no evidence for a higher background permethrin contamination in military bases located in Afghanistan compared to Germany. Daily use of permethrin impregnated BDU is associated with significantly higher permethrin uptake compared to the general population. Hand–mouth contact by smoking can increase uptake which also seems to be influenced by the duration of use of impregnated BDU.